Coral reefs for coastal protection: A new methodological approach and engineering case study in Grenada. (15th March 2018) - Reguero, Borja G.; Beck, Michael W.; Agostini, Vera N.; Kramer, Philip; Hancock, Boze
Abstract: Coastal communities in tropical environments are at increasing risk from both environmental degradation and climate change and require urgent local adaptation action. Evidences show coral reefs play a critical role in wave attenuation but relatively little direct connection has been drawn between these effects and impacts on shorelines. Reefs are rarely assessed for their coastal protection service and thus not managed for their infrastructure benefits, while widespread damage and degradation continues. This paper presents a systematic approach to assess the protective role of coral reefs and to examine solutions based on the reef's influence on wave propagation patterns. Portions of the shoreline of Grenville Bay, Grenada, have seen acute shoreline erosion and coastal flooding. This paper (i) analyzes the historical changes in the shoreline and the local marine, (ii) assess the role of coral reefs in shoreline positioning through a shoreline equilibrium model first applied to coral reef environments, and (iii) design and begin implementation of a reef-based solution to reduce erosion and flooding. Coastline changes in the bay over the past 6 decades are analyzed from bathymetry and benthic surveys, historical imagery, historical wave and sea level data and modeling of wave dynamics. The analysis shows that, at present, the healthy and well-developed coral reefs system in the southern bay keeps the shoreline in equilibrium and stable, whereas reef degradation in the northern bay is linked with severe coastal erosion. A comparison of wave energy modeling for past bathymetry indicates that degradation of the coral reefs better explains erosion than changes in climate and historical sea level rise. Using this knowledge on how reefs affect the hydrodynamics, a reef restoration solution is designed and studied to ameliorate the coastal erosion and flooding. A characteristic design provides a modular design that can meet specific engineering, ecological and implementation criteria. Four pilot units were implemented in 2015 and are currently being field-tested. This paper presents one of the few existing examples available to date of a reef restoration project designed and engineered to deliver risk reduction benefits. The case study shows how engineering and ecology can work together in community-based adaptation. Our findings are particularly important for Small Island States on the front lines of climate change, who have the most to gain from protecting and managing coral reefs as coastal infrastructure. Highlights: Coral reefs coastal protection is studied based on the effect on wave hydrodynamics. Six decades of historical coastline changes and wave climate are analyzed. A equilibrium long-term planform model shows reefs control the shoreline positioning. Severe coastal erosion occurs in areas not in equilibrium and with coral degradation. An innovative artificial reef design is described and field-tested.